Thin films of silicon nitride deposited at room temperature by non-reactive magnetron sputtering: radiofrequency power and deposition time influence on the formation of α-Si3N4 and its optical properties - Barrera-Mendivelso, Edwin Sebastian; Rodríguez-Gómez, Arturo (Frontiers in Physics, 2023)
Silicon nitride's excellent electronic and optical properties have positioned it as an indispensable element in silicon-based photonic platforms and photonic quantum computing. Chemical Vapor Deposition (CVD) and Plasma Enhanced CVD (PECVD) techniques predominate in high-performance silicon nitride thin film manufacture. Unfortunately, CVD and PECVD are expensive techniques that use hazardous gases and very high substrate temperatures. In this work, we used the sputtering technique to grow α-Si3N4 thin films at room temperature. We identified that by applying radiofrequency powers between 30 and 50 watts combined with deposition times below 120 minutes, we could achieve the growth of silicon nitride (SiNX) films with uniformly distributed crystalline particles, limited formation of clusters, and minimal alterations in atomic ordering. The Volmer-Weber model governs the film's growth, which favors its continuity and surface roughness. The optical bandgaps of our SiNX films ranged from 2.3 to 3.9 eV, and their RMS roughness never exceeded 4 nm. We observed a quasi-linear deposition rate concerning radiofrequency power and deposition time, whereby we were able to grow SiNX films controllably and reproducibly with thicknesses ranging from 45 to 500 nm.